O processo histórico do controle de constitucionalidade e as constituições do Brasil - Castanhato, Camila (2006)
Constitutionality control is maybe the most important subject for the Constitutional Law, as it is the mechanism that guarantees the existence of a true State of Right. The objective of this dissertation is to study the historical process that led to the creation of rule control mechanisms inside the law systems formally structured. In the first part, the birth of the control of rules system since Classic Antiquity is analised, and, in the second part, the evolution of the constitutionality control of rules in Brazilian constitutions is studied. An approach to the subject of rules in ancient Greece and Rome and in modern national states specially in England, in the United States, in France and in Austria is made, as well as the evolution in control of rules since our first Imperial Constitution of 1824 passing by all the others, i.e. Republican Constitution of 1891, 1934, 1937, 1946 and of 1967/1969 until the analysis of how the constitutionality control of laws in Brazilian present time is processed, supported by the Constitution of 1988